Effectiveness of Endovascular Intervention in the Treatment of Patients With Critical Ischemia of the Lower Limbs on the Background of Diabetic Heel Syndrome (Eurasian Research Bulletin, 2023)
The research work is based on the data of 47 patients with severe damage of severe diabetic heel syndrome (according to Wagner (1979) IV-V degree) who were examined and treated from 2019 to 2022 in the clinical base of Bukhara State Medical Institute of Bukhara Regional Multidisciplinary Medical Center.